2021
DOI: 10.1007/s11665-021-06302-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Polymeric Ester-Type Additives on the Performance of Metal Cutting Fluids for Machining of Titanium Alloy

Abstract: The introduction of additives to metal working fluid (MWF) compositions helps to reduce friction and wear while holding the possibility of sustainability to the environment. This study was performed to examine polymeric ester additives' influence on the MWFs performance during the drilling of a titanium alloy, Ti-6Al-4V, under a constant removal rate (MRR) of 4.2 mm 3 /s. The specific cutting energy (SCE) and build-up edge (BUE) were evaluated to assess the additives' performance in the MWFs. It was observed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Further work revealed that the performance of the phosphorusbased additive was a result of the introduction of phosphorus into the tribolayer within a critical temperature range and its lubrication failure temperature, and the activation temperature of phosphorus-based additive was influenced by the applied load [25,26]. However, additional work with polymeric ester additives revealed that the performance of each polymeric ester was also dependent on the drilling condition employed [27]. Thus, the cutting fluid additive performance depends on the drilling condition employed.…”
Section: Introductionmentioning
confidence: 99%
“…Further work revealed that the performance of the phosphorusbased additive was a result of the introduction of phosphorus into the tribolayer within a critical temperature range and its lubrication failure temperature, and the activation temperature of phosphorus-based additive was influenced by the applied load [25,26]. However, additional work with polymeric ester additives revealed that the performance of each polymeric ester was also dependent on the drilling condition employed [27]. Thus, the cutting fluid additive performance depends on the drilling condition employed.…”
Section: Introductionmentioning
confidence: 99%